Methodology of first-year students’ foreign language written discourse competency development - Iryna Hoshtanar (Revista EntreLínguas, 2021)
The article focuses on the issues of methodology of first-year students’ foreign language written discourse competency development. The aim of this paper is to present the results of experimental work on the development of first-year students’ foreign language written discourse competency and to specify the achievements in its implementation into the educational process at the Faculty of Foreign Philology of the Kherson State University. The subject of our research project is the methodology of the development of students’ written discourse competency as the basis for their written communication in a foreign language. The achievement of this goal was carried out in the course of solving a number of tasks. Thus, the notion of written discourse competency in a foreign language is considered and its structure and components are clarified. The methodology of university students’ foreign language written discourse competency development is presented in the form of a model which includes 5 components: target, concept, content, procedure and outcome. The results obtained in the course of the experimental teaching are given.